2023
DOI: 10.3389/fmicb.2023.1131836
|View full text |Cite
|
Sign up to set email alerts
|

Linking between soil properties, bacterial communities, enzyme activities, and soil organic carbon mineralization under ecological restoration in an alpine degraded grassland

Abstract: Soil organic carbon (SOC) mineralization is affected by ecological restoration and plays an important role in the soil C cycle. However, the mechanism of ecological restoration on SOC mineralization remains unclear. Here, we collected soils from the degraded grassland that have undergone 14 years of ecological restoration by planting shrubs with Salix cupularis alone (SA) and, planting shrubs with Salix cupularis plus planting mixed grasses (SG), with the extremely degraded grassland underwent natural restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 98 publications
0
0
0
Order By: Relevance
“…This demand is determined by the availability of environmental nutrients [54]. During the process of vegetation succession, vegetation and soil components are closely linked via increasing nutrient contents, improving soil physical properties (e.g., aggregate stability and water holding capacity), and promoting soil C sequestration [55], coevolved vegetation-soil interactions can significantly influence ecological processes [56]. Soil SOC and TN can provide C and N sources for microbial growth, affecting enzyme synthesis [15].…”
Section: Variations In Soil Extracellular Enzyme Activitymentioning
confidence: 99%
“…This demand is determined by the availability of environmental nutrients [54]. During the process of vegetation succession, vegetation and soil components are closely linked via increasing nutrient contents, improving soil physical properties (e.g., aggregate stability and water holding capacity), and promoting soil C sequestration [55], coevolved vegetation-soil interactions can significantly influence ecological processes [56]. Soil SOC and TN can provide C and N sources for microbial growth, affecting enzyme synthesis [15].…”
Section: Variations In Soil Extracellular Enzyme Activitymentioning
confidence: 99%
“…Moreover, previous studies have indicated that research on the driving environmental factors on the soil microbial community did not allow for a unified conclusion [34][35][36]. For example, Shu et al [37] identified soil pH as the most critical factor shaping bacterial community composition, but Cao et al [38] emphasized the importance of soil total phosphorus in shaping soil bacterial community diversity in Sanjiang plain. Therefore, the research on the structure and diversity of the soil microbial communities in the Sanjiang Plain wetland is full of controversy.…”
Section: Introductionmentioning
confidence: 99%